Psychometric validation of the Cardiac Distress Inventory - Short Form among people with cardiac diseases in Hong Kong - Fong, Ted C. T.; Leung, Ian C. H.; Wong, Chun Ka; Jackson, Alun C.; Ho, Rainbow Tin Hung (Frontiers in Psychiatry, 2024)
ObjectivesCardiac patients experience various somatic and psychosocial symptoms and stress is an important prognostic factor of cardiac rehabilitation. This study evaluated the psychometric properties of the 12-item Cardiac Distress Inventory – Short Form (CDI-SF) in the Chinese context.MethodsA total of 227 patients with cardiac diseases were recruited in a specialist outpatient clinic in Hong Kong between Aug 2022 and July 2023. The participants completed the CDI-SF and validated measures on psychosocial functioning and quality of life. Exploratory factor analysis and partial correlation analysis were conducted to examine the factorial validity, reliability, and convergent validity of the CDI-SF with reference to validating measures.ResultsThe 1-factor model showed adequate model fit with excellent composite reliability (ω = .92) and substantial factor loadings (λ = .64 –.94, p <.01). The CDI-SF factor was negatively associated with age (r = –.21, p <.01) and showed positive and strong partial correlations (r = .59 –.69, p <.01) with impact of event, depression, and burnout, and negative partial correlations (r = -.43 to -.54, p <.01) with resilience and quality of life.ConclusionOur study provides the first results on the psychometric properties of the CDI-SF among cardiac patients in Hong Kong. The psychometric results support the CDI-SF as a precise, valid, and reliable measure of cardiac distress in the Chinese context.